A randomized double-blind trial of 3 aspirin regimens to optimize antiplatelet therapy in essential thrombocythemia - Rocca, Bianca; Tosetto, Alberto; Betti, Silvia; Soldati, Denise; Petrucci, Giovanna; Rossi, Elena; Timillero, Andrea; Cavalca, Viviana; Porro, Benedetta; Iurlo, Alessandra; Cattaneo, Daniele; Bucelli, Cristina; et al. (Blood, 2020)
Essential thrombocythemia (ET) is characterized by abnormal megakaryopoiesis and enhanced thrombotic risk. Once-daily low-dose aspirin is the recommended antithrombotic regimen, but accelerated platelet generation may reduce the duration of platelet cyclooxygenase-1 (COX-1) inhibition. We performed a multicenter double-blind trial to investigate the efficacy of 3 aspirin regimens in optimizing platelet COX-1 inhibition while preserving COX-2–dependent vascular thromboresistance. Patients on chronic once-daily low-dose aspirin (n = 245) were randomized (1:1:1) to receive 100 mg of aspirin 1, 2, or 3 times daily for 2 weeks. Serum thromboxane B2 (sTXB2), a validated biomarker of platelet COX-1 activity, and urinary prostacyclin metabolite (PGIM) excretion were measured at randomization and after 2 weeks, as primary surrogate end points of efficacy and safety, respectively. Urinary TX metabolite (TXM) excretion, gastrointestinal tolerance, and ET-related symptoms were also investigated. Evaluable patients assigned to the twice-daily and thrice-daily regimens showed substantially reduced interindividual variability and lower median (interquartile range) values for sTXB2 (ng/mL) compared with the once-daily arm: 4 (2.1-6.7; n = 79), 2.5 (1.4-5.65, n = 79), and 19.3 (9.7-40; n = 85), respectively. Urinary PGIM was comparable in the 3 arms. Urinary TXM was reduced by 35% in both experimental arms. Patients in the thrice-daily arm reported a higher abdominal discomfort score. In conclusion, the currently recommended aspirin regimen of 75 to 100 once daily for cardiovascular prophylaxis appears to be largely inadequate in reducing platelet activation in the vast majority of patients with ET. The antiplatelet response to low-dose aspirin can be markedly improved by shortening the dosing interval to 12 hours, with no improvement with further reductions (EudraCT 2016-002885-30). •Most of the 245 patients with essential thrombocythemia who were treated with once-daily low-dose aspirin exhibit incomplete platelet inhibition.•In this randomized study, platelet inhibition was improved by twice-daily dosing, with no further inhibition using a shorter interval. [Display omitted]